Restarting after Business Discontinuity among Bumiputra Small and Medium Enterprises - Mohamad, Azlina; Rizal, Adriana Mohd.; Quoquab, Farzana; Juhdi, Noor Hasni; Sahimi, Musil (European Journal of Economics and Business Studies, 2015)
Small and Medium Enterprises (SMEs) entrepreneurial activities are critical to nation’s economic development and wealth creation. The governments provide both financial and non-financial assistances to support the development of these firms. Despite the government assistance, SMEs experience business discontinuity at the early stage of the firm development and unable to bounce back. Research on restarting after business discontinuity among SMEs is vital to enrich the existing literature in regards to firms’ learning and survival ability, and improving their current strategy to compete and sustain in the market. The objective of this study is to identify the factors that contribute to restarting after business discontinuity among Bumiputra Small and Medium Enterprises. This study utilized the case study methodology and selected Bumiputra firms under Majlis Amanah Rakyat as the research setting. The study found that five factors, including personality, environment, internal factor, resilience, and spiritual belief contributed to restarting after business discontinuity among Bumiputra SMEs. These findings broaden the theory of firm failure in entrepreneurship studies and their relations to firm learning. These insights are useful for both entrepreneurs of new firms and policy makers to improve entrepreneurial learning in supporting firms’ survival.